(untitled)
The mean cloudiness in 21-degree grid squares over the area extending from 30°N to 20°S and from 55°E to 100°E were computed from daily satellite observations of clouds for specific periods associated with a) late U K and normal onset of the monsoon, b) break in "the monsoon and (c) early and normal retreat of the monsoon in the years 1965,1966 and 1967. The isopleths of mean cloudiness in these specific periods were studied particularly in relation point to the mean large scale flow patterns over Asia and the neighbouring countries at the 500 and 300-mb levels. The daily avail- 500,300 and 200-mb charts during the retreating phases of the monsoon were also examined. The regions of development of maxima and minima of cloudiness have been discussed with reference to the large scale flow patterns and the L 0 lacunae in our present knowledge of the mechanism of these developments pointed out. The low pressure waves which, moved from east to west across the extreme south of peninsular India during the break period in August 1965, have Delhi for also been discussed in detail with reference to the isopleths of cloudiness and anomalies of rainfall. The significance of the observed persistent heavy cloudiness from 5°N to 5°Sacross the equator and the extension of the heavy cloudiness B in further to the south in the southern hemisphere during the break in the monsoon have also been discussed. , number=3, journal=MAUSAM, year=1971, month=Jul., pages=289–294